THE EFFECT OF PRIVATISATION ON SEAPORT PRODUCTIVITY: A DEA-MPI BASED COMPARATIVE ANALYSIS OF PRE- AND POSTCONCESSION AT THE DAR ES SALAAM MARITIME TERMINAL - MASSAMI, ERICK P.; NYANGE, CUTHBERT G. (Journal of Maritime Logistics, 2025)
Seaports are vital components of the global supply chain, and their efficiency and productivity are critical factors in facilitating international trade and economic development. In response to increasing competition and the need for enhanced performance, many governments around the world have pursued various port reforms, with terminal concessions being one of the most significant strategies. This study assesses the effect of privatisation on seaport productivity by comparing pre-concession operations under a public entity, i.e., Tanzania Ports Authority (TPA), with the post-concession operations under a private entity, i.e., Dubai Ports World (DP World), at Dar es Salaam seaport. The Data Envelopment Analysis-Malmquist Productivity Index (DEA-MPI) model is deployed to reveal the change in efficiency, technology, and productivity over a 12-month period of operations under each terminal operator. The findings show notable disparities in efficiency, technological, and productivity change over the period of analysis. More specifically, the privatisation of container operations has increased operational efficiency, and improved seaport technology and productivity over the period of analysis. The increase in productivity at Dar es Salaam seaport is exhibited in terms of increased cargo throughput and reduced ship turnaround time. The study concluded that terminal concessions can significantly enhance seaport performance when supported by positive efficiency change and technological change.